Effect of nurse‐led and physician‐led multidisciplinary team palliative care on quality of life, negative emotions, and pain for cancer patients: A meta‐analysis - Yunrong Li; Tiantian Wang; Yi Zhang; Yun Zhao (Precision Medical Sciences)
Abstract To systematically evaluate the effect of nurse‐led and physician‐led multidisciplinary team (MDT) palliative care models on quality of life, negative emotions, and pain for cancer patients. A comprehensive literature search of randomized controlled trials (RCTs) published in nine databases was conducted. Data analysis was performed using RevMan5.3. The findings were summarized using a random effects model of mean differences with 95% confidence intervals. The search strategy identified 15 articles involving 1850 cancer patients. MDT hospice care improved quality of life among cancer patients (SMD = 1.77, 95% CI [1.08, 2.46], Z = 5.02, p < .001), with nurse‐led care (SMD = 3.04, 95% CI [2.29, 3.79], Z = 7.95, p < .001) providing better effects than physician‐led care (SMD = 0.5, 95% CI [0.33, 0.67], Z = 5.76, p < .001). Furthermore, MDT hospice care significantly alleviated depression (SMD = –1.31, 95% CI [−1.49, −1.12], Z = 14.18, p < .001) and anxiety (SMD = –1.11, 95%CI [−1.29, −0.92], Z = 11.69, p < .001) and reduced patients' pain (SMD = –0.92, 95% CI [−1.13, −0.7], Z = 8.37, p < .001). Nurse‐led care provided better effects for relieving anxiety and depression, while physician‐led care provided better effects for relieving pain. The findings of the meta‐analysis indicate that MDT palliative care can improve the quality of life for cancer patients and alleviate their depression, anxiety and their pain. Nurse‐led care was superior in terms of quality of life, depression, and anxiety indicators, while physician‐led care had a more significant effect on pain relief.